دلائل النبوة المحمّدية وأبعادها التربوية من خلال كتاب "دلائل النبوة ومعجزات الرسول صلى الله عليه وسلم" لعبد الحليم محمود - دياب, سهيلة (جامعة الوادي university of eloued, 2023)
تهدف هذه الدراسة إلى محاولة تبيان دلائل النبوة ومعجزات الرسول صلى الله عليه وسلم وأبعادها التربوية في منظور الشيخ عبد الحليم محمود (رحمه الله) من خلال كتابه "دلائل النبوّة ومعجزات الرسول "، حيث جاء عنوانها موسوما بـ "دَلَائِلِ النُّبَوَّةِ المُحَمَّدِيَّةِ وَأَبْعَادِهَا التَّرْبَوِيَّةِ مِنْ خِلَالِ كِتَابِ "دلائل النبوّة ومعجزات الرسول " لعَبْدِ الحَلِيمِ مَحْمُود". وتظهر أهميّة البحث في التعرف على أهمّ الدلائل على نبوّته  التي بحثها الشيخ عبد الحليم محمود، وكذا في الأبعاد التربوية التي يستفيد منها المسلم في حياته. وقد اعتمدت أساسا على المنهج الوصفي والاستقرائي في عرض أهمّ الدلائل النبوية وأبعادها التربوية التي احتواها كتاب عبد الحليم محمود أنموذج الدراسة، ومن أهمّ النتائج المتوصَّل إليها أنّ الشيخ عبد الحليم محمود أفرد دلائل النبوة المحمدية عند الحديث عنها بأبعاد تربوية تساهم في استقامة سلوك المسلم وترسّخ القيم العقدية والتربوية لديه، كالتربية الحسنة للأبناء، والصدق والأمانة.This study aims to clarify the prophetic signs and its educational dimensions from the perspective of Sheikh Abd Al-Halim Mahmoud (may God have mercy on him) through his book "The signs of prophecy and the miracles of the Messenger, may the blessings of Allah be upon him!". The importance of the research is to identify the most important signs of his prophethood, may the blessings of Allah be upon him, which were researched by Sheikh Abd Al-Halim Mahmoud, as well as the educational dimensions that a Muslim benefits from in his life. I relied mainly on the descriptive approach in presenting the most important prophetic signs contained in Abd Al-Halim Mahmoud's book, the study model. One of the most important results reached is that Sheikh Abd Al-Halim Mahmoud singled out the signs of Muhammadan prophecy when talking about it with educational dimensions that contribute to the integrity of Muslim behavior and establish his doctrinal and educational values, such as the good education of children, the honesty and truthfulness.
عقيدة
Keywords: دلائل النبوة المحمدية- الابعاد التربوية - كتاب دلالئل النبوة ومعجزات الرسول- الشيخ عبد الحليم محمود " رحمه الله"; Evidence of Prophethood Muhammadiyah - Educational Dimensions - Book Evidence of Prophecy and Miracles of the Messenger - Sheikh Abdul Halim Mahmoud "may God have mercy on him"